2002
DOI: 10.1073/pnas.052713799
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase 2 blocks human cytomegalovirus replication

Abstract: Cyclooxygenase 2 (COX-2) mRNA, protein, and activity are transiently induced after infection of human fibroblasts with human cytomegalovirus. Prostaglandin E 2, the product of COX-2 activity, is transiently increased by a factor of >50 in cultures of virusinfected fibroblasts. Both specific (BMS-279652, 279654, and 279655) and nonspecific (indomethacin) COX-2 inhibitors can abrogate the virus-mediated induction of prostaglandin E2 accumulation. Levels of COX-2 inhibitors that completely block the induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
211
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(219 citation statements)
references
References 25 publications
7
211
1
Order By: Relevance
“…HCMV, while not having a COX-2 homolog, does upregulate cellular COX-2 upon infection, and COX-2 inhibitors prevent normal viral replication [65]. Lastly, RhCMV is able to block expression of interferon-stimulated genes (ISGs) by preventing activation of interferon regulatory factor-3 (IRF3) [66].…”
Section: Functional Characterizations Of Rhcmv Proteinsmentioning
confidence: 99%
“…HCMV, while not having a COX-2 homolog, does upregulate cellular COX-2 upon infection, and COX-2 inhibitors prevent normal viral replication [65]. Lastly, RhCMV is able to block expression of interferon-stimulated genes (ISGs) by preventing activation of interferon regulatory factor-3 (IRF3) [66].…”
Section: Functional Characterizations Of Rhcmv Proteinsmentioning
confidence: 99%
“…Previous studies have reported that production of COX-2 and PGE 2 modulates replication of human cytomegalovirus, gammaherpesvirus, and hepatitis B virus. [18][19][20] To investigate the possible mechanism(s) responsible for ASA-mediated down-regulation of HCV-RNA expression, we examined COX-2 activity, mRNA, and protein levels in ASAtreated HCV replicon cells. In this study, we found that 4 mM ASA treatment down-regulated COX-2 protein (Fig.…”
Section: Asa-mediated Down-regulation Of Hcv Expression Is Not Mediatmentioning
confidence: 99%
“…Of the isoforms of COX, COX-2 expression is stimulated under inflammatory conditions (28). Virus infection has been shown to stimulate COX-2 expression (29 -32), and inhibitors of COX-2 enzymatic activity attenuate virus replication (33,34), suggesting that the expression of COX-2 and the increased production of PGs may play an important role in viral replication. In addition, we and others have shown that under proinflammatory conditions the expression of COX-2 and iNOS appear to be coordinately regulated (35)(36)(37)(38).…”
mentioning
confidence: 99%